2014
DOI: 10.1210/en.2013-1843
|View full text |Cite
|
Sign up to set email alerts
|

Foxa1 and Foxa2 Regulate α-Cell Differentiation, Glucagon Biosynthesis, and Secretion

Abstract: The Forkhead box A transcription factors are major regulators of glucose homeostasis. They show both distinct and redundant roles during pancreas development and in adult mouse β-cells. In vivo ablation studies have revealed critical implications of Foxa1 on glucagon biosynthesis and requirement of Foxa2 in α-cell terminal differentiation. In order to examine the respective role of these factors in mature α-cells, we used small interfering RNA (siRNA) directed against Foxa1 and Foxa2 in rat primary pancreatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 44 publications
1
30
0
Order By: Relevance
“…The TF FOXA1 is not T-cell specific; it is involved in the regulation of cell differentiation under normal and pathological conditions (in epithelial, prostate and breast cancers; in epithelial cells of the intestines and lungs; and in pancreatic cells and other tissues 41, 42, 43, 44, 45, 46, 47 ). During embryonic stem cell development and hepatic differentiation, FOXA1 functions as a ‘pioneer TF' owing to its ability to engage condensed chromatin, bind nucleosome-assembled FOXA1 regulatory elements and displace repressive linker histones in response to retinoic acid treatment and transforming growth factor-β signaling.…”
Section: Discussionmentioning
confidence: 99%
“…The TF FOXA1 is not T-cell specific; it is involved in the regulation of cell differentiation under normal and pathological conditions (in epithelial, prostate and breast cancers; in epithelial cells of the intestines and lungs; and in pancreatic cells and other tissues 41, 42, 43, 44, 45, 46, 47 ). During embryonic stem cell development and hepatic differentiation, FOXA1 functions as a ‘pioneer TF' owing to its ability to engage condensed chromatin, bind nucleosome-assembled FOXA1 regulatory elements and displace repressive linker histones in response to retinoic acid treatment and transforming growth factor-β signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Baroukh et al demonstrated that miR‐124a2 expression was significantly increased by the e18.5 stage through analysis of the miRNA expression profiles during the e14.5d and e18.5d stages (important periods of pancreatic cell differentiation) in mouse embryonic pancreases . FOXA2 (forkhead transcription factor A2) is a major regulator of pancreas development, islet cell differentiation, and glucagon synthesis . Baroukh et al demonstrated that gene expression levels of FOXa2 was decreased in mouse pancreatic tissue when transfected with miR‐124 precursors, whereas the expression of FOXa2 protein was increased in mice transfected with anti‐miR‐124a2.…”
Section: Possible Associated Mechanism Between Mirnas and Dmmentioning
confidence: 99%
“…26 The combination of Foxa1 and Foxa2 (also known as hepatocyte nuclear factor (Hnf)) were shown to regulate Isl1 gene expression. 61 Hepatocyte nuclear factor (Hnf) family of transcription factors Several Hnf members have been implicated in the formation of the foregut endoderm from which the pancreas arises including Hnf1b, Hnf3b (hereafter called Foxa2) and Hnf6 (also called Onecut-1). [62][63][64][65] At e9.5, Hnf1b mutant mice lacked the ventral bud but a transient dorsal bud was present with temporal expression of Pdx1 and Hb9 (Table 1).…”
Section: Islet 1 (Isl1)mentioning
confidence: 99%